Essential Oils Prime Epigenetic and Metabolomic Changes in Tomato Defense Against Fusarium oxysporum - Soudani, Serine; Poza-Carrión, César; De la Cruz Gómez, Noelia; González-Coloma, Azucena; Andrés, María Fé; Berrocal-Lobo, Marta (Frontiers in Plant Science, 2022)
In this work, we studied the direct and indirect plant protection effects of an Artemisia absinthium essential oil (AEO) on tomato seedlings against Fusarium oxysporum sp. oxysorum radicis lycopersici (Fol). AEO exhibited a toxic effect in vitro against Fol. Additionally, tomato seedlings germinated from seeds pretreated with AEO and grown hydroponically were protected against Fol. Plant disease symptoms, including, water and fresh weight loss, tissue necrosis and chlorosis were less pronounced in AEO-treated seedlings. AEO also contributed to plant defenses by increasing callose deposition and the production of reactive oxygen species (ROS) on seed surfaces without affecting seed germination or plant development. The essential oil seed coating also primed a durable tomato seedling defense against the fungus at later stages of plant development. RNA-seq and metabolomic analysis performed on seedlings after 12 days showed that the AEO treatment on seeds induced transcriptomic and metabolic changes. The metabolomic analysis showed and induction of vanillic acid, coumarin, lycopene, an unknown metabolite of m/z 529 and oleamide in the presence of Fol. The StNRPD2 gene, the second largest component of RNA polymerases IV and V directly involved in de novo cytosine methylation by RNA-directed DNA methylation (RdDM), was highly induced in the presence of AEO. The host methionine cycle (MTC) controlling trans-methylation reactions, was also altered by AEO through the high induction of S-adenosyl methionine transferases (SAMts). Our results suggest that AEO treatment could induce de novo epigenetic changes in tomato, modulating the speed and extent of its immune response to Fol. The EO-seed coating could be a new strategy to prime durable tomato resistance, compatible with other environmentally friendly biopesticides.